THE ROLE OF ARTIFICIAL INTELLIGENCE TECHNOLOGY IN TEACHING ENGLISH - Fakhriddin Urinboevich Toshboltaev; Turgunboeva Oyshabibi Sarvarjon qizi (Ustozlar uchun, 2025)
This article examines how Artificial Intelligence (AI) is reshaping English language instruction. AI has brought significant changes to language learning by offering personalized and adaptive educational experiences. AI-powered tools support customized teaching approaches, allowing learners to receive focused assistance tailored to their specific language abilities, cognitive strengths, and developmental needs.